Flutter analysis of mistuned bladed disk - Yasutomo KANEKO; Makoto TAKEMURA; Kazushi MORI; Hiroharu OOYAMA (Nihon Kikai Gakkai ronbunshu, 2015)
Although, in designing blades, it is assumed that all blades on a disk are identical (tuned system), the vibration characteristics of the blade is slightly different due to the manufacturing tolerance, the deviation of the material property, and so on (mistuned system). As a result, in the forced response of an actual bladed disk caused by the flow distortion, the responses of all blades become different, and the response of a certain blade may become extremely large, due to the split of the duplicated natural frequencies, the distortion of the vibration modes, and so on. On the other hand, it is suggested by many researchers that the mistuning suppresses the blade flutter, because the complete travelling wave mode is not formed in a disk. In other words, the effect of the mistuning acts on the dangerous side for the forced vibration, while on the safety side for the blade flutter. In this study, the stability analysis of the mistuned bladed disk is carried out using the reduced model with high fidelity, in order to research the effect of mistuning on the blade flutter in detail. In the analysis, the actual bladed disk experienced the blade flutter is analyzed, and the calculated results are compared with the experienced phenomena, to verify the validity of the analysis method.